State territorialization at the margins: Property formalization and paperwork in the Ethiopian Somali frontier. Issue 116 (November 2020) - Emmenegger, Rony
Highlights: Property formalization is integral part of state territorialization. Paperwork mediates the inscription of law in property landscapes. Property landscapes entangle state authority symbolically and materially.